Work-family attitudes and beliefs: implications for future Air Force officers - Johnson, Stephanie K., author; Geroy, Gary, advisor; Hautaluoma, Jacob E., committee member; Feller, Richard W., committee member; Hall, Bruce, committee member (Colorado State University. Libraries, 2001)
Our surroundings are rich with environmental and associated paradigm shifts that influence work and family. There are many potential consequences of these shifts. These changes impact the very nucleus of work and family, and often result in conflict with the organization's culture as attempts are made to provide balance between work and family. A successful integration of work and family benefits both individuals and organizations within the Air Force and civilian workforce. An examination is provided that highlights future Air Force officers' expectations about balancing work and family life. Based on a current review of the literature, the Career Issues Survey was administered to a population of incoming Air Force officers to investigate attitudes toward various career and family issues. The sample for the study was comprised of 337 United States Air Force Academy and Reserve Officer Training Corps cadets preparing to enter the active duty Air Force. Results indicate significant differences between these groups regarding the degree of commitment women have to their career as compared to men. Significant gender differences were also present in such issues as career commitment, government or employer work-family policy responsibilities, and attitudes toward parental responsibility for childcare. The findings suggest that dealing with work-family issues should continue to be a concern for the Air Force. Incoming officers demonstrate an expectation that their new employer should provide benefits, practices and policies that promote work and family. Such efforts by the Air Force could: (1) potentially strengthen the performance of human resources, (2) be utilized as an added value within a recruiting strategy, and (3) prove to reduce attrition. Successful work-family balance solutions have the potential to strengthen the military force - a response that is vital to national society and society's development.
Keywords: vocational education; families and family life; personal relationships; sociology; individual and family studies